2016
DOI: 10.1200/jco.2016.66.7220
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Prospective Evaluation Comparing Intensity of Lymphodepletion Before Adoptive Transfer of Tumor-Infiltrating Lymphocytes for Patients With Metastatic Melanoma

Abstract: Adoptive cell transfer, the infusion of large numbers of activated autologous lymphocytes, can mediate objective tumor regression in a majority of patients with metastatic melanoma (52 of 93; 56%). Addition and intensification of total body irradiation (TBI) to the preparative lymphodepleting chemotherapy regimen in sequential trials improved objective partial and complete response (CR) rates. Here, we evaluated the importance of adding TBI to the adoptive transfer of tumorinfiltrating lymphocytes (TIL) in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
202
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 307 publications
(219 citation statements)
references
References 34 publications
4
202
0
Order By: Relevance
“…several clinical trials testing tumor infiltrating lymphocytes (TIL) (8)(9)(10) and receptor-engineered T cells (11). Similarly, infusion of less-differentiated T cell subsets that coexpress lymphoid homing markers like CD62L or costimulatory markers such as CD27 are associated with greater tumor regression (12)(13)(14).…”
Section: Introductionmentioning
confidence: 98%
“…several clinical trials testing tumor infiltrating lymphocytes (TIL) (8)(9)(10) and receptor-engineered T cells (11). Similarly, infusion of less-differentiated T cell subsets that coexpress lymphoid homing markers like CD62L or costimulatory markers such as CD27 are associated with greater tumor regression (12)(13)(14).…”
Section: Introductionmentioning
confidence: 98%
“…A classic example of this type of therapy is the adoptive T-cell transfer in malignant melanoma, in which peritumoral T cells are extracted and activated and propagated outside the body. After transfer of these activated T cells, a long-lasting response could be detected in over 25% of the tumors [31].…”
Section: Passive Vaccinationmentioning
confidence: 95%
“…Retrospective studies have demonstrated a response rate of 16% with approximately 6% with prolonged survival over 10 years [2]. By collection, expansion and reintroduction of a patient's existing tumor infiltration lymphocytes, adoptive cell transfer therapy has demonstrated a response rate as high as 53% in a 'highly select population' [22].…”
Section: Alternative Front-line Therapies To Immune Therapiesmentioning
confidence: 99%